Combined effects of feed-grade urea and a urease inhibitor on growth performance, digestibility, blood biochemical indicators, and rumen environment in beef cattle - Zhou, Yuan; Song, Xuerong; Fu, Dabo; Robles-Jimenez, Lizbeth E.; Gonzalez-Ronquillo, Manuel; Ghavipanje, Navid (Frontiers in Veterinary Science, 2025)
This study evaluated the combined effects of feed-grade urea (FGU) and a urease inhibitor (HyUrit) as a partial replacement for vegetable protein sources, specifically soybean meal (SBM), in beef cattle diets. The outcomes assessed included growth performance, nutrient digestibility, blood parameters, and the rumen environment. A total of 30 Simmental bulls [average initial body weight (IBW): 445.67 ± 26.48 kg] were assigned to a completely randomized design (CRD) and fed diets containing FGU supplemented with 0, 5, 10, 15%, or 20% of a urea inhibitor (HU) on a dry matter (DM) basis. There were no significant dietary effects on IBW (p = 0.843), final body weight (FBW; p = 0.912), or average daily gain (ADG; p = 0.372). Similarly, the intakes of DM (p = 0.906), organic matter (OM; p = 0.939), crude protein (CP; p = 0.898), neutral detergent fiber (NDF; p = 0.565), and acid detergent fiber (ADF; p = 0.616) were not affected by dietary treatments. However, supplementation with HU at 10, 15, and 20% significantly improved the digestibility of OM (p = 0.001), CP (p = 0.030), NDF (p = 0.001), and ADF (p = 0.001) compared to the FGU group; the digestibility of DM (p = 0.651) remained unaffected. Neither nitrogen intake (g/d, p = 0.898; g/LW0.75, p = 0.707) nor nitrogen balance (g/d, p = 0.614; g/LW0.75, p = 0.755) was significantly affected by different levels of urease inhibitor supplementation. Additionally, dietary treatment did not significantly affect the plasma concentrations of alkaline phosphatase (ALP; p = 0.319), albumin (p = 0.080), insulin (p = 0.217), or insulin-like growth factor-I (IGF-I; p = 0.094) in beef cattle. However, the activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were significantly increased in the HU15 group (15% HyUrit), with p-values of 0.002 and 0.011, respectively. In addition, total plasma protein concentration was significantly lower in the HU20 group compared to both the Ctrl and HU5 (5% HyUrit) groups (p = 0.012). In vitro, ammonia nitrogen (N-NH3) production at 0 h (p = 0.0001), 0.5 h (p = 0.0009), and 2 h (p = 0.0001) was higher in both the FGU- and HyUrit-containing groups than in the Ctrl (SBM) group. Overall, the lower cost of FGU may justify its partial replacement of true protein meals in beef cattle diets without compromising growth performance or animal health, especially in cases where FGU is consumed as a single dose rather than through a total mixed ration (TMR) at the HU20 level (20% HyUrit), thereby mitigating the risk of alkalosis.